Work on Text and Dictionaries Based on the Book "The Last Days" in Their Language (Journal of Pedagogical Inventions and Practices, 2022)
Practical analysis of methodological recommendations aimed at questioning the ability of students to work on text and dictionaries in their language and to work in text and dictionaries based on the book The Last Days